Anonymous Authentication Scheme for Intercommunication in the Internet of Things Environments - Youngseok Chung; Seokjin Choi; Dongho Won (International Journal of Distributed Sensor Networks)
Authentication and privacy protection are important security mechanisms for keeping things safe in the Internet of Things environments. In particular, an anonymous authentication scheme is a privacy preserving authentication technique which provides both authentication and privacy preservation. An authentication scheme with anonymity in mobility networks was proposed recently. However, it was proven that it failed to provide anonymity against passive adversaries and malicious users and security against known session key attacks and side channel attacks. We propose an anonymous authentication scheme for intercommunication between the things in the Internet of Things environments. The proposed scheme provides not only anonymity and security, but also untraceability for the thing. Moreover, we only use low cost functions, such as hash functions and exclusive-OR operations in consideration of limited computing power of the thing.